2005
DOI: 10.1002/chem.200400936
|View full text |Cite
|
Sign up to set email alerts
|

Tin‐Free Radical Alkoxyamine Addition and Isomerization Reactions by Using the Persistent Radical Effect: Variation of the Alkoxyamine Structure

Abstract: Various C-centered radicals can efficiently be generated through thermal C-O-bond homolysis of alkoxyamines. This method is used to perform environmentally benign radical cyclization and intermolecular addition reactions. These alkoxyamine isomerizations and intermolecular carboaminoxylations are mediated by the persistent radical effect (PRE). In the paper, the effect of the variation of the alkoxyamine structure--in particular steric effects in the nitroxide moiety--on the outcome of the PRE mediated radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 47 publications
(46 reference statements)
2
18
0
1
Order By: Relevance
“…[211] It was found that replacing the TEMPO moiety in the starting alkoxyamine with sterically more hindered nitroxides provides compounds which undergo thermal radical carboaminoxylation with 1-octene in higher yields (up to 86 % yield) in a much shorter reaction time (1.5 h). [212] The reaction time for the radical carboaminoxylation of 1-octene with alkoxyamine 102 to give 103 was reduced to ten minutes by switching to microwave heating. [213,214] More recently, microflow radical carboaminoxylations of 1-octene and other olefins by using the sterically highly hindered alkoxyamine 104 were reported.…”
Section: Alkoxyamine Additions To Various Radical Acceptorsmentioning
confidence: 99%
“…[211] It was found that replacing the TEMPO moiety in the starting alkoxyamine with sterically more hindered nitroxides provides compounds which undergo thermal radical carboaminoxylation with 1-octene in higher yields (up to 86 % yield) in a much shorter reaction time (1.5 h). [212] The reaction time for the radical carboaminoxylation of 1-octene with alkoxyamine 102 to give 103 was reduced to ten minutes by switching to microwave heating. [213,214] More recently, microflow radical carboaminoxylations of 1-octene and other olefins by using the sterically highly hindered alkoxyamine 104 were reported.…”
Section: Alkoxyamine Additions To Various Radical Acceptorsmentioning
confidence: 99%
“…These unusual properties have led to a wide range of applications spanning their use in biology as spin labels [1][2][3][4][5][6] to the development of organomagnetic materials. 7 In organic chemistry, nitroxides have been used in kinetic studies, [8][9][10][11] as oxidizing species in the form of the corresponding N-oxo ammonium salts, [12][13][14][15][16][17][18][19][20][21][22][23] as temporary caps for transient carbon radicals, [24][25][26][27][28][29][30][31] and as probes for stereocontrol with prochiral carbon radicals. [32][33][34][35][36] In polymer chemistry, nitroxide-mediated polymerization (NMP) [37][38][39][40][41][42][43][44][45][46][47] has become popular as a method for preparing living polymers ...…”
Section: Introductionmentioning
confidence: 99%
“…142 The activation energy for C-O bond homolysis depends upon the stability of both radicals and the structure of the nitroxide. Increasing the steric bulk of the nitroxide results in a far more efficient C-O bond homolysis; 2,6-di-tert-butyl nitroxide reacts over 4-fold faster than the standard TEMPO nitroxide, whilst one of the most effective nitroxides is the ethyl derivative 151 (Fig.…”
Section: Alkoxyamines and The Persistent-radical Effectmentioning
confidence: 99%